Generation z's behavior in sharing travel moments - Grace Christien Sumakul; Aditya Pandowo (Universitas Merdeka Malang, 2024)
Tourism activities are community activities to provide pleasure and can be done by various circles of society, including Generation Z who will later become leaders and policymakers. The birth period of those accustomed to the digital world makes social media the primary tool for carrying out tourism activities especially sharing their travel moments. This study aims to identify the behaviour of Generation Z in sharing travel moments using EFA and CFA and then analyse the relationship of factors and social media to the motivation formed using T-test analysis and One Way ANOVA. As a result, Generation Z share their travel moments because the Factor of Getting recognition and the Factor of Providing Information. The relationship of social media users in sharing Generation Z travel moments from WhatsApp users like more private relationships specifically for their close friends. TikTok users like to have groups with the same fun. Instagram users want to add a touch of art to the photos/videos shared and Facebook users like to provide information about their activeness on social media. This research has an impact on entrepreneurs and the government to take advantage of the influence of social media in increasing tourist visits especially Generation Z